If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -23 = x + 1 Reorder the terms: -23 + 9x = x + 1 Reorder the terms: -23 + 9x = 1 + x Solving -23 + 9x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -23 + 9x + -1x = 1 + x + -1x Combine like terms: 9x + -1x = 8x -23 + 8x = 1 + x + -1x Combine like terms: x + -1x = 0 -23 + 8x = 1 + 0 -23 + 8x = 1 Add '23' to each side of the equation. -23 + 23 + 8x = 1 + 23 Combine like terms: -23 + 23 = 0 0 + 8x = 1 + 23 8x = 1 + 23 Combine like terms: 1 + 23 = 24 8x = 24 Divide each side by '8'. x = 3 Simplifying x = 3
| xsquared+9x+16=8 | | 3+2x=3(2+x) | | 7*(18+4)-13= | | 9+5x-3x=27 | | 4n+n+4=16-(n) | | 3x+4=-32 | | -6x-30= | | -6x+10=-56 | | 12x^2y^2+29x^2y= | | 4n+n+4=16-n | | 2(6y+3z-1)=12y+3z-1 | | 3x+70-7x= | | x-(8)=-2 | | 4x-8x=-24 | | 4x/7-4=12 | | 8n-4=12 | | x-(9)=-7 | | 12c-6=10c+4 | | 3a+11=4a+8 | | 4/5x+3=5x | | 4g-9=(-3g)+12 | | 2/3(3x+12)=32 | | 3(x+5)+4=3x+4 | | .2x^2+16x=0 | | 42=-6(-2x-3) | | 5(2x+3)-2=-2(x+4) | | 6(7x+3)=354 | | -3/7x+4 | | M/2=m-2/3 | | 4(-2x-5)=-76 | | 3p=9p-12 | | (15,625a^-18b^3c^24)^1/6 |